Hesitance in acceptance of dental implants as a treatment modality amongst adult population of Jazan region - A singlecenter study (Bangladesh Journal of Medical Science, 2024)
Objective The present survey was aimed to evaluate and assess the patient’s knowledge and hesitance regarding implant treatment as an alternative to the fixed dental prosthesis in the Jazan region, Saudi Arabia.Materials and methods This self-explanatory cross-sectional survey was completed over two months. A questionnaire was designed, and a pilot study was performed with 20 participants to assess the reliability and validity of the questions. Finally, 149 participants took part in the survey. The questions were divided into two sections. Section I: inquiries related to the demographic status, and section II: evaluate knowledge and hesitance to opt for implant therapy as a treatment option. A significant association between the variables was measured by employing a oneway ANOVA test. A p-value of < 0.05 has been considered a statistically significant level.Results and discussion 149 participants, with 104 (69.8%) males and 45 (30.2%) females, answered the questionnaire. About 79 (53.3%) participants had adequate knowledge about implant therapy. The majority of participants, 104 (73.8%), thought implant-supported dentures required meticulous care. The reason for abstaining from implant denture as a substitute for missing teeth showed that 111 (74.5%) patients felt the treatment was costly, followed by fear of unknown side effects (56.6%) participants, fear of pain 55.7% of participants, increased in the duration of therapy (46.3%) patients and requirement for surgery. No statistical significance was measured between the variables (p